2022
DOI: 10.1038/s41419-022-05415-2
|View full text |Cite
|
Sign up to set email alerts
|

SphK-produced S1P in somatic cells is indispensable for LH-EGFR signaling-induced mouse oocyte maturation

Abstract: Germ cell division and differentiation require intimate contact and interaction with the surrounding somatic cells. Luteinizing hormone (LH) triggers epidermal growth factor (EGF)-like growth factors to promote oocyte maturation and developmental competence by activating EGF receptor (EGFR) in somatic cells. Here, we showed that LH-EGFR signaling-activated sphingosine kinases (SphK) in somatic cells. The activation of EGFR by EGF increased S1P and calcium levels in cumulus-oocyte complexes (COCs), and decrease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Interestingly, the immature COCs could not induce NPPC expression in the ampullae. The maturation of COCs is induced by LH-activated EGFR signaling in cumulus cells [ 10 , 11 ]. In our study, the activation of EGFR by EGF promoted TGFB1 expression in cumulus cells, and the addition of TGFB1 promoted NPPC expression in the ampullae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the immature COCs could not induce NPPC expression in the ampullae. The maturation of COCs is induced by LH-activated EGFR signaling in cumulus cells [ 10 , 11 ]. In our study, the activation of EGFR by EGF promoted TGFB1 expression in cumulus cells, and the addition of TGFB1 promoted NPPC expression in the ampullae.…”
Section: Discussionmentioning
confidence: 99%
“…During oestrus, luteinizing hormone (LH) from the pituitary acts on mural granulosa cells to induce the expression of epidermal growth factor (EGF)-like growth factors. Then, EGF receptor (EGFR) signaling is activated in cumulus cells, resulting in the maturation of COCs [ 10 , 11 ]. The mature COCs are picked up and transported into the oviductal ampulla for fertilization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stat3 fl/fl mice and Fshr-Cre mice were kindly provided by Hua Yu from (Beckman Research Institute of City of Hope, CA) and Youqiang Su (Shandong University, Qingdao, China), respectively. Since the FSH receptor promoter is only expressed in granulosa cells, we generated granulosa cell-specific STAT3 knockout mice to better explore the specific mechanisms by which IL-22 affects granulosa cells by crossing Stat3 fl/fl mice with Fshr-Cre mice [ 15 ]. The mice were maintained under controlled temperature and lighting conditions (12-h light:12-h darkness cycle) with free access to food and water in a specific pathogen-free (SPF) facility.…”
Section: Methodsmentioning
confidence: 99%
“…Our study found that SKI-349 inhibited the AKT/mTOR signaling pathway in HCC cell lines, which might be due to the fact that: (1) SKI-349 inhibited SPHK, which led to ceramide accumulation in HCC cells and activated phosphatases (including protein phosphatase 1 and protein phosphatase 2A), thus inactivating the AKT/mTOR cascade (Lin et al 2006). (2) As mentioned above, SKI-349 inhibited SPHK1 and SPHK2 activity (Hengst et al 2020); meanwhile, the decrease of SPHK1 and SPHK2 activity reduced S1P and further inhibit AKT/mTOR cascade reaction in HCC cell lines (Yuan et al 2022). Thus, SKI-349 was hypothesized to inhibit the AKT/mTOR signaling pathway by suppressing SPHK1-and SPHK2-regulated S1P.…”
Section: Accepted Manuscript 13mentioning
confidence: 99%